Prevalence of diabetes in Poland: a combined analysis of national databases. Issue 10 (24th April 2019) - Topor‐Madry, R.; Wojtyniak, B.; Strojek, K.; Rutkowski, D.; Bogusławski, S.; Ignaszewska‐Wyrzykowska, A.; Jarosz‐Chobot, P.; Czech, M.; Kozierkiewicz, A.; Chlebus, K.; Jędrzejczyk, T.; Mysliwiec, M.; et al.
Abstract: Aims: To assess the number of people with diabetes in Poland using combined national sources and to evaluate the usefulness of data from an insurance system for epidemiological purposes. Methods: The data were collected from four sources: 1) 2013 all‐billing records of the national insurance system comprising people of all age groups undergoing procedures or receiving services in primary healthcare, specialist practices and hospitals and also those receiving drugs; 2) an epidemiological study, NATPOL, that involved the assessment of people with undiagnosed diabetes; 3) the RECEPTOmetr Sequence study on prescriptions; and 4) regional child diabetes registries. Results: In 2013, 1.76 million people (0.98 million women and 0.79 million men) had medical consultations (coded E10‐E14) and 2.13 million people (1.19 million women and 0.94 million men) purchased drugs or strip tests for diabetes. A total of 0.04 million people who used medical services did not buy drugs. In total, the number of people with diabetes in the insurance system was 2.16 million (1.21 million women and 0.95 million men), which corresponds to 6.1% (95% CI 6.11–6.14) of women and 5.1% (95% CI 5.12–5.14) of men. Including undiagnosed cases, the total number of people with diabetes in Poland was 2.68 million in 2013. Conclusion: The estimated prevalence of diabetes (diagnosed and undiagnosed cases) in Poland is 6.97%. Data from the national insurance system with full coverage of the population can be treated as a reliable source of information on diseases with well‐defined diagnosis and treatment methods, combined with an assessment of the number of undiagnosed individuals. What's new?: The present study is a unique attempt to assess diabetes prevalence in one of the biggest countries in Central and Eastern Europe. The prevalence of diabetes estimates presented to date rely on studies covering selected populations in different regions of Poland. The present analysis was conducted on the basis of a complete database of contracted medical services and reimbursed drugs from the only public insurance in the country and from population studies (NATPOL and POLSENIOR), and led to a diabetes prevalence estimate of 6.97%. The study shows the high burden of diabetes and the need for a complete diabetes register for monitoring health needs and diabetes control.